CLINICOPATHOLOGICAL STUDY OF CARCINOMA LARYNX - DR.SHIVKUMAR RAGHUVANSHI; DR.SUNIL KUMAR SINGH BHADOURIYA; DR.SUSHIL GAUR; DR.VIVEK KUMAR PATHAK (International Journal of Pharma and Bio Sciences, 2015)
This study was done to determine the risk factors and clinico-pathological pattern of the laryngeal malignancies.Patients were studied with particular importance to the mode ofpresentation, risk factors, topography and histopathology of the tumour.Out of 100 patients, 96 were males and 4 were females with male to female ratio of24:1. Maximum number of cases belonged to age group 51-60 years.Tobacco intake in the form of smoking was the major risk factor and present in 76% of cases.Commonest presenting symptom was the dysphagia. Supraglottic area was the commonest site (72%) forlaryngeal cancer in this study. Squamous cell carcinoma was found in 98% of patients. Moderately differentiatedcategory seen in 48% of patients. Most of the patientspresented in the stage III and IV(30% and 52%). 54 (54%) cases out of 100 cases had cervical lymph node metastasis at the time of presentation.Diagnosis is based on direct or indirect visualization of the larynx, supplemented by CT scan and confirmed by histopathological examination.